Buku sumber matematik diagnostik dan pemulihan - Yudariah Mohammad Yusof; Mohamad Rashidi Md. Razali; Ali Hassan Mohd. Murid; Maslan Osman; Md. Nor Bakar, 1955-; Mohd. Salleh Abu, 1958-; Ong, Chee Tiong; Roselainy Abdul Rahman; Sabariah Baharun (Skudai : Universiti Teknologi Malaysia, 2002)
41